Forward-oriented design for learning: illustrating the approach - Yannis Dimitriadis; Peter Goodyear (Association for Learning Technology, 2013)
This paper concerns sustainable approaches to design for learning, emphasising the need for designs to be able to thrive outside of the protective niches of project-based innovation. It builds on the “in medias res” framework and more specifically on a forward-oriented approach to design for learning: one that takes a pro-active design stance with respect to each of the phases of an extended lifecycle. We draw on fieldwork notes and interview data to describe two cases that illustrate some of the key features of the approach. Recommendations for further R&D in the area of design for learning are provided, derived from the theoretical framework, and illustrated in this paper.